Professionalism and Religiosity: A Thematic Interpretation Study on Muslim Workers in Indonesia - Elkhairati, Elkhairati; Arsal, Arsal; Imran, Maizul (AJIS: Academic Journal of Islamic Studies, 2024)
The work challenges of developed countries, such as; (Indonesia) are characterised by the demands of professionalism in fierce work competition. There is a need for a new approach to the terminology of Quran-based professionalism to give maximum results to Muslims who reflect religious aspects. This research aims to understand the interpretation of the Quranic verses related to work professionalism and elaborate its meaning and to find out the opportunities for Quran-based work professionalism terminology to be applied to work demands in the modern era. The research method uses literature study with a qualitative-descriptive approach through thematic interpretation model. The results of the study found; that the terminology of professionalism can be combined with `ahsanu 'amalan and `atqana in the verse which indicates grade and quality in accordance with the field of expertise accompanied by aspects of piety. Known professionalism can be developed into religious-professionalism. It is undeniable that the modern world requires workers to adapt to the changes of the industrial revolution 4.0. The aspect of religiosity is really likely to improve the quality of international work professionalism.